2021
DOI: 10.3389/fcimb.2021.770612
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cryptosporidium spp. in Yaks (Bos grunniens) in China: A Systematic Review and Meta-Analysis

Abstract: Cryptosporidium spp., the causative agent of cryptosporidiosis, can infect a variety of hosts. So far, there has been limited information regarding Cryptosporidium spp. infection in yaks (Bos grunniens). Here, we performed the first systematic review and meta-analysis for Cryptosporidium spp. infection in yaks in China. To perform the meta-analysis, five databases (Chinese National Knowledge Infrastructure (CNKI), VIP Chinese journal database, WanFang Data, PubMed, and ScienceDirect) were employed to search fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…However, previous studies have indicated that the prevalence of Cryptosporidium spp. in younger cattle is higher than that in adult cattle(Geng et al 2021;Li et al 2020). As the host of Cryptosporidium spp., cattle are usually primarily infected by C. bovis, C. parvum, C. andersoni and C. ryanae(Gong et al 2017).…”
mentioning
confidence: 92%
“…However, previous studies have indicated that the prevalence of Cryptosporidium spp. in younger cattle is higher than that in adult cattle(Geng et al 2021;Li et al 2020). As the host of Cryptosporidium spp., cattle are usually primarily infected by C. bovis, C. parvum, C. andersoni and C. ryanae(Gong et al 2017).…”
mentioning
confidence: 92%
“…In addition to genetics, age, herd and farm environment, feeding practices, poor management and other complications, the most important factor is infection (5,6). Many countries, including China, have experienced calf diarrhea outbreaks of differing degrees caused by pathogens, such as Cryptosporidium, BRV, BCoV, E. coli K99 and other pathogens (7)(8)(9)(10). According to the annual report of Japan in 2017, the economic losses caused by BRV in the previous years were estimated to be about 1 billion yen (11).…”
Section: Introductionmentioning
confidence: 99%